Avaliação sobre administração de medicamentos pela equipe de enfermagem de um hospital pediátrico: estudo transversal - Macedo, Raquel Chaves de (Universidade Federal do Tocantins, 2021)
This study aimed to investigate the evaluation of nursing assistants and technicians regarding the implementation of safety practices for medication administration in a children's hospital. This is a cross-sectional study conducted at a Children's Hospital in the State of Tocantins, with nursing assistants and technicians. The work was approved by the local Research Ethics Committee (CAAE08269319.0.0000.5519) and the data collection occurred in the months of January and February 2020. The professionals answered a questionnaire consisting of two parts, the first referring to the demographic characterization and professional, and the second, a validated instrument containing 27 items. The items contained responses related to the performance of professionals in medication administration, with scores from one to five, one related to the most unsafe practice and the five to the safest and most desirable professional practice. The data were stored in spreadsheets built in Microsoft Excel for Windows 2010® and treated using descriptive statistics. 40 nursing technicians and assistants participated in the research, a value that corresponds to approximately 34,2% of the total of these professionals who work in the hospital. The sample consisted of the majority of nursing technicians (87.5%, n = 35) and women (97.5%, n = 39). The average age of professional aging was 40.5 years (SD = 7.78), who had an average professional experience of 18.5 years (SD = 3.54). Most participants (62.5%, n = 25) did not receive admission training at the hospital where a survey was conducted. It was also identified that the items with the lowest scores (1, 2 and 3), that is, the actions that professionals performed less frequently (worse scores), were related to questions about taking only the prescribed drugs to bed, returning such as leftover medication to the pharmacy and administer medication verbally only in emergency cases. The items with the best responses (5) were related to checking the patient's name, verifying the route, dose and pharmaceutical form of the prescribed medication. The points that have lower scores, indicate weaknesses in the medication process and, therefore, must be corrected through permanent education in the health service, encouraging the patient's safety culture and specific training on the medication process in the hospital.